“It May Be Risky but the Experience Is Worth It”: Risk Perceptions of International Students in the U.S. - Ravert, Russell D.; Fatin N. Asnan (Journal of Interdisciplinary Studies in Education, 2023)
Studying abroad provides excellent opportunities for growth, but can also bring new uncertainties and risks. In this exploratory study, female international students studying in the U.S. (n=29) responded to open-ended questions designed to understand better the types of risks they experience and the ways they respond. Inductive content analysis identified a set of five thematic categories: a) social risk, b) danger risk, c) daily task risk, d) self-development risk, and e) isolation risk. Students reported dealing with these uncertainties through a combination of weighing risks through information and trusting others, playing it safe at times, but pressing forward in other situations to make the most of opportunities.